Gambaran Tekanan Darah, Frekuensi Nadi Dan Kecemasan Pasien Pre Operasi Phacoemulsifikasi Di Rumah Sakit Bhakti Asih Brebes - Usmanto, Uus; Dwi Retno Sulistyaningsih; Retno Setyawati (An-Najat, 2025)
Phachoemulsification is a cataract surgical technique that uses ultrasinicvibrationts to crust the cataract and suction out lens fragments through a small incicion in the cornea. This technique allows for the placement of a foldable intraocular lens and allows for a quick recovery because the incision is small and does not require stitches. Phacoemulsification is useful for many types of cataracts but is less effective for dense cataracts. This study uses a quantitative descriptive reserch type aimed at decribing certain characteristics or phenomena of the reserch subjecht without testing hypotheses or causal relationships. In this context, blood pressure data, pulse rate and anxiety levels are measured and presented in the form of numbers, descriptive statistics such as averages, presentages, or frequency distributions.  From the result of the reserch data shows that as many as 43 respondens (57,33%) have normal blood pressure, for pulse frequency shows the results that as many as 44 respondents (58,67%) have normal pulse frequency. And for anxyety shows the results that as many as 42 respondents (56,00%)have mild anxiety. based on the result of the study that has been conducted it can be concluded that the majority of respondents’ ages are in the category elderly (>60 years) with a total of 59 respondenst (78.67%). The majority of female gender is 43 respondent (57.33%). While the majority of respondents’ health history who do not haveblood pressure increases is 45 respondents (60%). And for the blood pressure variable, the results show that as many as 43 respondents (57.33%) have normal blood pressure, for the pulse frequency variable, the results show that as many as 44 respondents (58.67%) have normal pulse frequency, while for anxiety, the results show that as many as 42 respondents (56%) have mild anxiety.